Synergistic effect of workplace well-being and business growth on productivity - Gustavo Emiliano Mascareño Beltran; Itzel Alejandra Lara Manjarrez (Revista Venezolana de Gerencia)
This study explored the synergistic effect of workplace well-being and business growth on the productivity of Small and Medium-sized Enterprises (SMEs) in the trade sector in Sinaloa, Mexico. The Workplace-Business Synergy Theory (WBST) was proposed and validated, proposing that the positive interaction between workplace well-being and business growth creates a multiplicative impact on productivity. The study aimed to analyze the relationships between these variables and validate the Workplace-Business Synergy Index (WBSX) as a measurement tool. A quantitative study was conducted by administering surveys to SME employees, and the data were analyzed using Pearson correlations, linear regressions, and structural equation modeling. The results revealed a strong and significant relationship between workplace well-being and productivity (r = 0.849, p < 0.001), as well as between business growth and productivity (r = 0.756, p < 0.001). Furthermore, business growth was found to mediate the relationship between workplace well-being and productivity, supporting the WBST. The WBSX demonstrated excellent internal consistency (Cronbach’s alpha = 0.96) and strong confirmatory factor validity. The findings suggest that fostering workplace well-being and business growth can lead to significant productivity gains. In conclusion, the study confirms that the strategic interaction between workplace well-being and business growth generates a synergistic effect that significantly enhances productivity. This relationship, supported by robust statistical evidence, highlights the importance of considering both variables jointly to understand and improve organizational performance in SMEs.